Liberalism: the basics - Charvet, John; I. Title (London : Routledge, 2019)
"John Charvet's Liberalism is lively, opinionated, full of examples, and always admirably clear. The route from practices to values to theory takes the reader from actual liberal societies to its inner architecture. Anyone wanting to know what liberalism stands for and why, need look no further than this book." - Jonathan Seglow, Royal Holloway, University of London, UK."This is a lively and original introduction to liberalism. Charvet articulates a distinctive understanding of liberalism as set of practices embedded in modern social life and provides an engaging exploration of the role played by liberal ideas in contemporary political controversies." - Cillian McBride, Queen's University Belfast, UK.
1. The idea of a practice and the initial distinction between liberal and illiberal societies -- 2. The rule of law -- 3. Free speech -- 4. Freedom of association and movement -- 5. Economic freedom -- 6. Sexual freedom -- 7. The idea and value of freedom -- 8. The equality of the participants -- 9. Community -- 10. Liberalism and human well-being -- 11. Libertarian theories -- 12. Utilitarian theories of liberalism -- 13. Kant's idea of freedom as rational self-determination -- 14. Contemporary theories of liberalism.
Includes bibliographical references and indexes
Keywords: 1. Liberalism